Percutaneous left atrial appendage occlusion using different technologies in the United Kingdom: A multicenter registry. Issue 3 (21st September 2016) - Betts, Timothy R.; Leo, Milena; Panikker, Sandeep; Kanagaratnam, Prapa; Koa‐Wing, Michael; Davies, David Wyn; Hildick‐Smith, David; Wynne, Dylan G.; Ormerod, Oliver; Segal, Oliver R.; Chow, Anthony W.; Todd, Derick; et al.
Abstract : Objectives: This study aimed at assessing the feasibility and long‐term efficacy of left atrial appendage occlusion (LAAO) in a "real world" setting. Background: Although LAAO has recently emerged as an alternative to oral anticoagulants in patients with atrial fibrillation for the prevention of thromboembolic stroke, "real world" data about the procedure with different devices are lacking. Methods: Eight centers in the United Kingdom contributed to a retrospective registry for LAAO procedures undertaken between July 2009 and November 2014. Results: A total of 371 patients (72.9 ± 8.3 years old, 88.9% males) were enrolled. The overall procedure success was 92.5%, with major events in 3.5% of cases. The device choice was Watchman in 63% of cases, Amplatzer Cardiac Plug in 34.7%, Lariat in 1.7%, and Coherex WaveCrest in 0.6%. A significant improvement in procedure success (from 89.2% to 95.7%; P = 0.018) and reduction of acute major complications (from 6.5% to 0.5%; P = 0.001) were observed between procedures in the first and the second half of the recruitment time. An annual 90.1% relative risk reduction (RRR) for ischemic stroke, an 87.2% thromboembolic events RRR, and a 92.9% major bleeding RRR were observed, if compared with the predicted annual risks based on CHADS2, CHA2DS2‐Vasc, and HAS‐BLED scores, respectively, over a follow‐up period of 24.7 ± 16.07 months. Conclusions: LAAO can be performed safely in a real world setting with good implant success rates and procedural outcomes. The long‐term benefits of the procedure are reassuring in terms of both ischemic events and avoidance of severe bleeding associated with anticoagulation in this patient group. © 2016 Wiley Periodicals, Inc.